2015
DOI: 10.1097/fjc.0000000000000273
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Endothelial Microparticles Induced by Different Therapeutic Drugs for Infantile Hemangioma

Abstract: Endothelial microparticles (EMPs) are complex vesicular structures with great significance in vascular pathophysiology. Here, we aimed to determine the impact of therapeutic drugs for infantile hemangioma, a common vascular tumor of infancy, on the biochemical features of EMPs. We exposed human umbilical vein endothelial cells to propranolol (Pro), dexamethasone (Dex), or rapamycin (Rap). Compared with controls, Pro and Rap dramatically augmented EMP release, whereas Dex significantly suppressed EMP generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…At present, the regulation of the release of microvesicles from endothelial cells by glucocorticoids is poorly characterized: A study by Thai et al [38] demonstrated that dexamethasone triggers the release of annexin A1-containing microparticles from endothelial cells, while Zhu et al [39] reported that dexamethasone inhibits the constitutive release of microparticles from human umbilical vein endothelial cells. We assume that different endothelial cell types show a different response to glucocorticoids, since the function of umbilical vein endothelial cells, a fenestrated renal endothelial cell and a very tight endothelial cell in the stem cell niche of the hippocampus, to name a few examples, have very different functions.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the regulation of the release of microvesicles from endothelial cells by glucocorticoids is poorly characterized: A study by Thai et al [38] demonstrated that dexamethasone triggers the release of annexin A1-containing microparticles from endothelial cells, while Zhu et al [39] reported that dexamethasone inhibits the constitutive release of microparticles from human umbilical vein endothelial cells. We assume that different endothelial cell types show a different response to glucocorticoids, since the function of umbilical vein endothelial cells, a fenestrated renal endothelial cell and a very tight endothelial cell in the stem cell niche of the hippocampus, to name a few examples, have very different functions.…”
Section: Discussionmentioning
confidence: 99%
“…As we previously described, 19 human umbilical vein endothelial cells (HUVEC) were harvested by primary culture from human umbilical cord veins. HUVEC between passage 2 and 7 were used for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…For miRNA detection, 250 ng of RNA was subject to cDNA synthesis and real‐time PCR using SYBR PrimeScript miRNA RT‐PCR kit (Takara, Japan). The quantitative real‐time PCR analysis was performed on a 7900HT Real‐Time PCR System (Applied Biosystems, USA) using standard conditions as we described previously (Zhu et al , ). All mRNA primers were synthesized by Sangon Biotech and were designed using PrimerBank, a validated resource for PCR primers (Wang et al , ), while miRNA‐specific primers were purchased from GeneCopoeia.…”
Section: Methodsmentioning
confidence: 99%